Performance of the Kraft Mill Biosolids Compost and Their Quality Evaluation. Issue 3 (1st October 2020) - Neubauer, M. E.; Miranda, J. P.; Ramírez, F.; Esquerra, A.; Vidal, G.
Abstract: The goal of this article is the evaluation of the compost quality from Kraft mill organic matter by germination Raphanus sativus and Lepidium sativum. The evaluation of compost was measured in terms of stability, maturity and phytotoxicity. Two compost piles were elaborated, one with a ratio of C/N = 23.67 and the other with C/N = 18.67. Each pile was divided into 2 sections, pile 1 (compost 1 and 2) and pile 2 (compost 3 and 4). Wood bark was added to each pile as a structuring material, resulting in mixtures conformed by treatment sludge with bark. The results obtained show that all the mixtures reached thermophilic temperatures (>50 °C), resulting in stable and mature compost with humic and fulvic acid ratios > 1.9. The gemination index showed no presence of toxic substances, with germination percentages over 80% for all the tests of Raphanus sativus and Lepidium sativum, while the N:P:K ratio of 0.5 of Compost 4 positively and significantly boosted the growth of both species with respect to control. It was concluded that Compost 4, with C/N ratio = 23.67 with structuring material presented positive and significant results ( p > 0.05) with respect to Compost 1, 2 and 3.